Cross-class 3D object synthesis guided by reference examples. (February 2016) - Su, Xiaoyu; Chen, Xiaowu; Fu, Qiang; Fu, Hongbo
Abstract: Re-combining parts of existing 3D object models is an interesting and efficient technique to create novel shape collections. However, due to the lack of direct parts' correspondence across different shape families, such data-driven modeling approaches in literature are mostly limited to the synthesis of in-class shapes only. To address the problem, this paper proposes a novel approach to create 3D shapes via re-combination of cross-category object parts from an existing database of different model families. In our approach, a reference shape containing multi-functional constituent parts is pre-specified by users, and its design style is then reused to guide the creation process. To this end, the functional substructures are first extracted for the reference shape. After that, we explore a series of category pairs which are potential replacements for the functional substructures of the reference shape to make interesting variations. We demonstrate our ideas using various examples, and present a user study to evaluate the usability and effectiveness of our technique. Abstract : Graphical abstract: Abstract : Highlights: We propose to use a structurally complex reference shape to guide cross-class 3D object synthesis. We present an HSD based descriptor to match substructures between the reference shape and the database shapes to establish the correspondences. We introduce a heuristic category suggestion mechanism to reuse the reference shape to synthesize composite models.